Time adaptive dynamic simulation of rigid bodies - Giang, Thanh (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2004)
Traditionally the maintenance of high constant frame rates for real-time performance relied on level of detail simplification, usually performed within the geometry domain. However, simplification can also be achieved for simulation if physical plausibility rather than physical accuracy is acceptable.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin